2022
DOI: 10.3390/w14050797
|View full text |Cite|
|
Sign up to set email alerts
|

Joint Effects of the DEM Resolution and the Computational Cell Size on the Routing Methods in Hydrological Modelling

Abstract: Natural disasters, including droughts and floods, have caused huge losses to mankind. Hydrological modelling is an indispensable tool for obtaining a better understanding of hydrological processes. The DEM-based routing methods, which are widely used in the distributed hydrological models, are sensitive to both the DEM resolution and the computational cell size. Too little work has been devoted to the joint effects of DEM resolution and computational cell size on the routing methods. This study aims to study t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 68 publications
0
5
0
Order By: Relevance
“…For example, Liu et al (2011) has concluded that DEM cell size significantly influenced the calculation of the L factor in a 0.88 km 2 watershed in the lowlands of northern Germany. Similarly, Li et al (2016) and Kruk et al (2020) have found that the S factor was more sensitive to changes in DEM cell size than the L factor, and the value of the LS factor decreased to 1/6-1/3 of its value when the DEM cell size increased from 30 m to 1000 m. These findings indicated that the DEM cell size can greatly affect the simulation accuracy of the USPED models by influencing the value of topographic factor (LS).…”
mentioning
confidence: 87%
“…For example, Liu et al (2011) has concluded that DEM cell size significantly influenced the calculation of the L factor in a 0.88 km 2 watershed in the lowlands of northern Germany. Similarly, Li et al (2016) and Kruk et al (2020) have found that the S factor was more sensitive to changes in DEM cell size than the L factor, and the value of the LS factor decreased to 1/6-1/3 of its value when the DEM cell size increased from 30 m to 1000 m. These findings indicated that the DEM cell size can greatly affect the simulation accuracy of the USPED models by influencing the value of topographic factor (LS).…”
mentioning
confidence: 87%
“…As usual in hydrological modeling practice, the DEM was aggregated to a coarser spatial resolution (1 km) to drastically reduce the computational load of the simulations, while preserving a good level of detail in representing the main hydrological processes (see e.g., Aerts et al, 2022;Li et al, 2022 for discussion on result dependency on resolution in hydrologic models). For the inundation model, where a more detailed representation of the local morphology is required, the original DEM resolution (∼30 m) was maintained.…”
Section: Hazard Modeling Chainmentioning
confidence: 99%
“…To succeed in this, one relies on model calibration [1]. There are many parameters that affect rainfall-runoff models [2,3]. More parameters can be used, and more accurate results can be obtained with increasing computer processing power.…”
Section: Introductionmentioning
confidence: 99%